The incidence and pattern of geriatric limb fractures in Ibadan, Nigeria - Ogunrewo, Tolulope O.; Oyewole, Olugboyega A.; Omoyeni, Richard A.; Iken, Chuka T.; Ogunlade, Samuel O. (International Journal of Research in Medical Sciences, 2020)
Background: Individuals within the geriatric age group sustained different types of fractures as such the need to determine the incidence and pattern of limb fractures among patients 65 years and above admitted through the accident and emergency department of the University College Hospital Ibadan. Methods: A retrospective hospital-based study in which patients 65 years and above admitted through the accident and emergency department of the University College Hospital Ibadan over a 42-month period were involved in the study. Using a proformal completed from the electronically stored data that captures the patient’s history, examination findings, X-ray film and treatment offered which was collected on a weekly basis. Results: 12.58% of the patients reviewed within the study period were geriatric patients. A total of 98 geriatric patients were reviewed. There were 59 female and 39 male with a ratio 1.5:1. The fractures were mostly secondary to a trivial fall within their homes (68.37%) while traumatic injury from motor vehicle and motor bike crashes accounted for 11.22% and 16.33% respectively. The most commonly fractured bone is the femur and the proximal third is the most affected part. Comminuted fracture is the most common pattern observed. Conclusions: More than 10% of the reviewed population was in the geriatric age group and the proximal femur was the most commonly fractured bone in this age group. They usually follow trivial falls.